Ideological Conflict in Rembang (Case Study: Cement Mining Conflict in Rembang) - Puryanto, Sidik; Siswanto, Romi (Jurnal Ilmiah Peuradeun, 2024)
The ongoing conflict in Watuhputih has escalated into a contentious and complex issue that continues to capture public attention. The debates have given rise to a fierce clash of ideas, concepts, and interpretations of laws, ultimately leading to numerous lawsuits. This study uses a qualitative research approach with Wehr and Bartos analysis to analyze conflict dynamics in the cement factory conflict case in Rembang, Central Java. The qualitative method used a case study. Data collection techniques used in-depth interviews with sources from 20 informants and documentation from various mass media. The results of this study indicate that conflict dynamics are divided into pre-conflict, confrontation, and crisis. This study concludes that the conflict in Rembang has turned into an ideological conflict. Each group claims that the ideology understood the most correct between environmental sustainability, traditional and modern, capitalist. A dark history of conflict and prolonged dynamics causes ideological conflicts. The record of the conflict’s journey into a social movement in Rembang is a series of conflicts between the community and small-scale mining companies previously in conflict areas from the 90th year.